Resilient and Accelerated Scale-Up of Subcutaneously Administered Depot–Medroxyprogesterone Acetate in Nigeria (RASuDiN): A Mid-Line Study in COVID-19 Era - Osinowo K; Sambo-Donga F; Ojomo O; Ibitoye SE; Oluwayemi P; Okunfulure M; Ladipo OA; Ekholuenetale M (Dove Medical Press, 2021)
Kehinde Osinowo,1 Fintirimam Sambo-Donga,1 Oluwaseun Ojomo,1 Segun Emmanuel Ibitoye,1 Philip Oluwayemi,1 Morounfola Okunfulure,1 Oladapo Alabi Ladipo,1 Michael Ekholuenetale1,2 1Association for Reproductive and Family Health, Trade and Convention Center, Abuja, Nigeria; 2Department of Epidemiology and Medical Statistics, Faculty of Public Health, College of Medicine, University of Ibadan, Ibadan, NigeriaCorrespondence: Kehinde Osinowo Email osinowo.k@arfh-ng.orgBackground: Injectable contraceptives are fast becoming the method of choice among women in sub-Saharan Africa (SSA). Specifically, the subcutaneously administered depot-medroxyprogesterone acetate (DMPA-SC) is gaining traction as a convenient, private and effective method to address unmet need for family planning (FP). The objective of this study was to determine the trend in DMPA-SC use in Nigeria.Methods: Data was extracted from the National Health Management Information System (NHMIS) FP register on DMPA-SC uptake in public health facilities and through community-oriented resource providers (CORPS) in 10 Nigerian states. The linear trend model was adopted in data analysis based on lowest measure of dispersion and/or highest adjusted coefficient of determination (R2). The statistical significance was determined at 5%.Results: There was an upward trend in the use of DMPA-SC among clients who received the service through health providers, CORPS and self-injection in the 10 project states over a period of 12 months (August 2019-July 2020). In addition, the linear trend model showed that for every unit increase in months, the average number of women expected to use DMPA-SC through health providers, CORPS and self-injection will increase by 1308.3 (Yt = 3799.7 +1308.3*t), 756.73 (Yt = − 1030.8 +756.73*t) and 77.864 (Yt = − 159.7 +77.864*t) respectively. In all models, the adjusted coefficient of determination was 99.9% which showed good model fitness. The results also showed that the number of DMPA-SC clients varied across the project states with Niger (32,988) and Oyo (31,511) states reporting the highest number of clients over the period of 12 months.Conclusion: There was an increasing use of DMPA-SC and self-injection among clients over time. Health facility and community-based FP programs should be strengthened to ensure improved access to FP services.Keywords: family planning, contraceptive, Nigeria, DMPA-SC, self-injection, birth control